Towards Transformational Research for and with Indigenous Communities: The New British Columbia Indigenous Child Welfare Research Network - de Finney, Sandrina; Green, Jacquie; Brown, Leslie (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2009)
This article documents the development of the newly launched Indigenous Child Welfare Research Network in British Columbia. This Network is a provincial association of researchers, service providers, community members and policy makers with an interest in using Indigenous research in the transformation of child and family services. Rooted in a vision for healing and the inclusion of diverse voices, Network Initiatives seek to reclaim Indigenous ways of knowing and doing and reposition them at the core of child and family wellness initiatives. The Network provides a space for critical dialogue about Indigenous research, as well as opportunities for researched-related training, knowledge transmission and resource sharing.